A leitura da imagem no livro didático de língua portuguesa (PNLDM: por uma política de formação de leitores da imagem na educação brasileira - Passos, Edson Rodrigues (2013)
The present study arose from the observation concrete and real, in the classroom, the reading difficulties of students (elementary and middle school) before imagistic texts in textbooks in Portuguese. The study investigates the presence of the image as language form composite ideological signs, from the perspective of public policy in education in Brazil. Justified the study in view of its importance for the Brazilian educational society, in order to understand how images in textbooks contribute (or not) to consolidate legislation normalized by LDB / PCN / PNLD. We developed the following central research question: Who are these Public Policy? This concern with the use of images in textbooks by the NCPs / LDB and PNLD is service quality in the teaching-learning Brazilian Education? Or is intrinsic to capitalist aspects and market current through a liberal? The study aims to search the general importance and forms of application and use the image in English Language Teaching in the textbook, with a view to effecting Legislation Public Policy Education (LDB / PCN / PNLDm. Specific objectives and : 1) Analyze the images chosen by the authors in textbooks, mainly seeking to understand: the ideological transmission and power relationship in order to lead the student to a fixed worldview that prevents the development of critical thinking, 2) investigate the power of the media image portrayed in textbooks as an element of alienation of learners; 3) Understand how images in textbooks are intrinsically linked aspects capitalists and market today, in this sense, what images we are offering our students, who are building values; 4) Examine the non-appropriation of the school through the world of images. In Chapter 1 presents an overview of the methodological approach and broad, objectives, problem statement and conceptual thinkers who have their theoretical foundations of Marxism - historical materialism and dialectical philosophy of language Bakhtin. In the 2nd chapter, presents itself through the Marxist view a material analysis of the conditions of the present, trying to find the hidden contradiction in public policy education, especially in the context of the mode of production and reproduction of life within the capitalist system, without losing view the state as a central category and its political effects. In the 3rd chapter addresses the issue of the Brazilian Education Textbook and the importance of educating readers of nonverbal, analyzing the relationship between language, image and power. The proposal of the 4th and 5th chapters is to analyze the discourse of images presented in the textbooks of Portuguese Language PNLDM - National Textbook Program (High School) 2010 collection. In conclusion, the core of this work consists in gradually overcoming the threshold of reading instrumental character positivist proposal in textbooks and other show trials and offers significant resume playback of images in textbooks in Portuguese